New insights into the pathogenesis and detection of Mycoplasma pneumoniae infections. (December 2008) - Waites, Ken B; Balish, Mitchell F; Atkinson, T Prescott
Mycoplasma pneumoniae is a common cause of upper and lower respiratory tract infections in persons of all ages and may be responsible for up to 40% of community-acquired pneumonias. A wide array of extrapulmonary events may accompany the infections caused by this organism, related to autommunity or direct spread. This review includes a discussion of the latest knowledge concerning the molecular pathological basis of mycoplasmal respiratory disease, how the organism interacts with the host immune system and its association with the development of chronic conditions such as asthma, recent emergence of macrolide resistance and the status of laboratory diagnostic methods.